Welfare Impact of Organic Fertilizer Adoption: Empirical Evidence From Nigeria - Oyetunde-Usman, Zainab; Ogunpaimo, Oyinlola Rafiat; Olagunju, Kehinde Oluseyi; Ambali, Omotuyole Isiaka; Ashagidigbi, Waheed Mobolaji (Frontiers in Sustainable Food Systems, 2021)
Soil fertility depletion is acknowledged to adversely influence agricultural productivity and welfare status of rural farming households. Studies have shown that organic fertilizer utilization tends to rejuvenate the soil, thereby enhancing its productive capacity. This study seeks to estimate the welfare impact of organic fertilizers adoption among agricultural households using the 2018/2019 Nigeria General Household Survey. The novelty of this study is in the use of the propensity score matching and endogenous treatment regression to address biases that may arise from both observed and unobserved factors. Results show that the adoption of organic fertilizers positively and significantly impacts the welfare of farmers, particularly when sources of unobserved characteristics of agricultural households are accounted for. The heterogeneity impacts results show that female household heads, agricultural households that had access to credit, and farm households’ residents in the Southern region of Nigeria significantly gained more from the adoption of organic fertilizers. In addition, robustness checks reveal that adoption of organic fertilizers does not result in an immediate welfare effect, the effect is however positive and significant over time. This suggests that adoption does not only improve soil and mitigate against climate impact, but it also has a higher likelihood of providing long-term and sustainable welfare impact for agricultural households. The results point to the need for policies and programmes to promote and sustain the adoption of organic fertilizers among non-adopters and to sustain adoption among adopters through addressing existing institutional barriers such as extension and credit facilities.